Experiences of violence and discrimination among LGBTQ+ individuals during the COVID-19 pandemic: a global cross-sectional analysis. Issue 9 (21st September 2022) - Adamson, Tyler; Lett, Elle; Glick, Jennifer; Garrison-Desany, Henri M; Restar, Arjee
Abstract : Objectives: To characterise the extent to which the levels of violence and discrimination against lesbian, gay, bisexual, transgender and queer (LGBTQ+) people have changed amid COVID-19. Design: Cross-sectional, secondary analysis. Setting: 79 countries. Participants: All adults (aged ≥18 years) who used the Hornet social networking application and provided consent to participate. Main outcome measure: The main outcome was whether individuals have experienced less, or the same or more levels of discrimination and violence from specific groups (eg, police and/or military, government representatives, healthcare providers). Results: 7758 LGBTQ+ individuals provided responses regarding levels of discrimination and violence. A majority identified as gay (78.95%) and cisgender (94.8%). Identifying as gay or queer was associated with increased odds of experiencing the same or more discrimination from government representatives (OR=1.89, 95% CI 1.04 to 3.45, p=0.045) and healthcare providers (OR=2.51, 95% CI 0.86 to 7.36, p=0.002) due to COVID-19. Being a member of an ethnic minority was associated with increased odds of discrimination and violence from police and/or military (OR=1.32, 95% CI 1.13 to 1.54, p=0.0) and government representatives (OR=1.47, 95% CI 1.29 to 1.69, p=0.0) since COVID-19. Having a disability was significantly associated with increased odds of violence and discrimination from police and/or military (OR=1.38, 95% CI 1.15 to 1.71, p=0.0) and healthcare providers (OR=1.35, 95% CI 1.07 to 1.71, p=0.009). Conclusions: Our results suggest that despite the upending nature of the COVID-19 pandemic, around the world, government representatives, policymakers and healthcare providers continue to perpetuate systemic discrimination and fail to prevent violence against members of the LGBTQ+ community.